Implementation Of Multicultural-Based Character Values To Remind Tolerance For Diversity In Social Studies Learning (Exploratory Study on MTs Students) - Iswan Riyadi (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Multicultural Education plays a major role in Indonesian educational institutions. Our cultural, racial, religious, socioeconomic, and other distinctions are seen as particularly strong selling points for the United States. Although God has blessed us with a wide variety of people and cultures, this diversity frequently leads to friction between different social groupings and even individuals. Integrating ethical and spiritual principles into the classroom is what's known as "Character Education." Multicultural approaches to teaching and learning in the social studies might help defuse the tensions and conflicts that have arisen as a result of SARA, particularly in Indonesia. Students will develop more empathy and acceptance of those of different backgrounds if they study multicultural social issues. The purpose of this research is to assess how well students' religious tolerance incorporates Multicultural-Based Character Values into their social studies curriculum. Researchers used a qualitative methodology and conducted case studies for this investigation. Interviews, field notes, and other forms of documentation are used. Reduction, data presentation, and conclusion drawing/verification are the three methods of data analysis. The findings revealed that many children continue to have difficulties in communicating and interacting with both instructors and classmates as a consequence of linguistic and cultural differences. This causes several social behaviors in students, including low empathy, lack of mutual respect, and individualism. So, it is felt that there is a need to internalize multicultural values, especially the value of religious tolerance, togetherness, and mutual help, in the hope that students can coexist peacefully. The supporting factor is students' high motivation (internal and external motivation) and support from all Madrasah residents. In contrast, the inhibiting factor is the significant negative influence on students from the inappropriate environment.